An assessment of the preservation practices of the BusinessWorld Publishing Corporation Library - Pepito, Samuel M. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
This study looks into the existing preservation practices of the Business World Publishing Corporation Library. An emphasis is placed on the status of newspaper preservation in these institutions. The researcher looked into three important aspects of preservation: the awareness and participation of individuals safeguarding the collection, the actual over-all condition of the entire collection, and the policies and prevalent practices in the organization.